FOSTERING STUDENTS’ VOCABULARY THROUGH BUSY PICTURES AT PAUD ZALFA NAQIYYA SAMARINDA - Lusiana, Rizky Ayu; Khatimah, Khusnul (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Vocabulary mastery is a crucial aspect of English language proficiency, yet many students struggle to understand and use vocabulary accurately. Visual media such as busy pictures are believed to support early childhood vocabulary development through visual stimulation and interactive engagement. Therefore, this study was conducted to determine the effectiveness of using busy pictures in improving vocabulary mastery among Group B students at PAUD Zalfa Naqiyya Samarinda. This research employed a quantitative method, involving a population of 32 students from Group B during the 2023/2024 academic year, with a sample of 13 students. The findings revealed that the average pretest score before treatment was 21.31, while the average post-test score after the use of busy pictures increased to 54. This represents a 32.69% improvement. The results indicate that busy pictures are an effective medium for enhancing students’ vocabulary mastery. Furthermore, the hypothesis testing showed that the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted, confirming the positive impact of busy picture media on vocabulary acquisition.